Implementasi nilai-nilai karakter dan keteladanan K. H. Ahmad Dahlan pada Siswa Kelas 2 SDN Sadang - Dwi Purwanti, Mei; Hendratno; Istiq’faroh, Nurul (CV. Kurnia Grup, 2023)
The purpose of this study was to determine the value of character and example taught by K.H. Ahmad Dahlan to grade 2 students of SD Negeri Sadang, Sidoarjo Regency. This research method uses qualitative research methods with descriptive qualitative research types, the subject of this research is 25 grade 2 elementary school students at SD Negeri Sadang, Taman District, Sidoarjo Regency. Data collection techniques use observation, interview and documentation techniques. The results of this study show that there are several character values of K.H Amad Dahlan instilled, the results of the study show that there are 4 character values and examples instilled in grade 2 students by SD Negeri Sadang Taman District, Sidoarjo Regency, namely religious, nationalist, honest and integrity values, education karam The instilled in SD Negeri Sadang, Taman District, Sidoarjo Regency instilled character education in accordance with the teachings of K.H. Ahmad Dahlan.